2021
DOI: 10.2196/17503
|View full text |Cite
|
Sign up to set email alerts
|

A User-Centered Chatbot (Wakamola) to Collect Linked Data in Population Networks to Support Studies of Overweight and Obesity Causes: Design and Pilot Study

Abstract: Background Obesity and overweight are a serious health problem worldwide with multiple and connected causes. Simultaneously, chatbots are becoming increasingly popular as a way to interact with users in mobile health apps. Objective This study reports the user-centered design and feasibility study of a chatbot to collect linked data to support the study of individual and social overweight and obesity causes in populations. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 61 publications
(53 reference statements)
0
14
0
1
Order By: Relevance
“…Those in the control group underwent 7 in-person counseling sessions with a health care professional, whereas those in the intervention group interacted with the PathMate 2 chatbot daily with 4 in-person counseling sessions (61%) [ 36 ]. Other studies (19/23, 83%) either used chatbots mainly to collect data on diet, physical activity, sitting time, and sleep [ 31 , 32 ] or were still in the developmental stage. Future studies should consider adopting an experimental design that evaluates the use of chatbots on objective weight-related outcomes such as weight loss, diet (eg, food choices, calorie intake, and consumption frequency), and physical activity (eg, energy expenditure, activity type, and activity frequency) using inferential statistics that suggest repeatability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Those in the control group underwent 7 in-person counseling sessions with a health care professional, whereas those in the intervention group interacted with the PathMate 2 chatbot daily with 4 in-person counseling sessions (61%) [ 36 ]. Other studies (19/23, 83%) either used chatbots mainly to collect data on diet, physical activity, sitting time, and sleep [ 31 , 32 ] or were still in the developmental stage. Future studies should consider adopting an experimental design that evaluates the use of chatbots on objective weight-related outcomes such as weight loss, diet (eg, food choices, calorie intake, and consumption frequency), and physical activity (eg, energy expenditure, activity type, and activity frequency) using inferential statistics that suggest repeatability.…”
Section: Resultsmentioning
confidence: 99%
“…Other techniques used in text-based chatbots were the delivery of colloquial, personally and culturally appropriate conversational tones and content [ 26 , 30 ]; emojis to emulate human emotional expressions [ 30 - 32 ]; positively framed words [ 32 ]; citations of credible information sources [ 26 , 33 ]; and validation (eg, acknowledgments and compliments) of not only behaviors but also thoughts and feelings [ 41 ]. Participants of the included studies were also found to have appreciated the personification of the chatbot (eg, funny, animated, empathetic, or playful) [ 25 , 29 , 31 , 32 , 37 ] and the provision of real-time, fast, and reliable recommendations [ 26 , 29 , 38 ]. In addition, studies (9/23, 39%) that enabled speech, instead of just text-based chatbot interactions (including those that use augmented reality [AR]) [ 29 ], improved engagement through a more convenient hands-free voice interaction with the chatbot [ 34 , 43 - 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example is Forksy, which monitors users' healthy eating behavior ( 13 ). A telegram chatbot Wakamola also serves as a valuable tool to assess individuals' obesity risk based on their sociodemographics, diet, physical activity, BMI, and social lifestyles ( 26 ). A preliminary review of AI chatbot-based physical activity and diet interventions revealed that more than half of the reviewed chatbots successfully deliver behavior change strategies through increased user motivation and engagement ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…After pooling more than 400 members of the UPV community, the final design was selected, including the name of the chatbot: Wakamola. Wakamola is registered in the UPV technical catalogue and produced three research articles: the first one presented the chatbot and the data collected [Asensio-Cuesta et al, 2021a], the second analysed the lifestyle changes registered in the chatbot due to the COVID-19 confinement [Asensio-Cuesta et al, 2021b]. Finally the third article explored the differences between the three pilots performed using Wakamola [Asensio-Cuesta et al, 2021c].…”
Section: Other Contributionsmentioning
confidence: 99%